Ionospheric Regional modeling Algorithm based on GNSS Precise Point Positioning - Chen, Yan (My University, 2021)
Precise point positioning (PPP) is an absolute spatial positioning technology different from carrier phase relative positioning. With the continuous development of Global navigation satellite system (GNSS), multi-constellation GNSS further provides PPP with more abundant observation information and useful spatial geometric observations, which improves positioning performance and robustness. In recent years, the un-difference and un-combined precise point positioning (UPPP) has been continuously developing. Firstly, we introduce the basic theory of GNSS positioning and compare the position performance between UPPP and ionospheric-free PPP (IF PPP). The positioning performance of the four mainstream GNSS systems, GPS, GLONASS, Galileo, and Beidou, the PPP floating-point solutions of the four satellite systems all converge within 60 minutes and their error are less than 10cm. Secondly, a two-dimensional (2-d) model is proposed to fit the vertical total electronic content (VTEC) in the ionosphere with the ionospheric delays extracted by UPPP. With the model constraining the ionospheric delay in UPPP, the convergence is 2 minutes shorter than using the global ionospheric map (GIM) from IGS. Thirdly, to solve the limitation of the traditional methods in 2d representation, a method is proposed represent the ionosphere in 3D, called Compressed Sensing Tomography (CST). Comparing the simulated single-difference slant total electron content (STEC) and the input single- difference STEC between satellites, the root mean square (RMS) of the reference station’s error is less than 1 TEC unit
Keywords: Precise point positioning (PPP), Ionospheric delay, mathematical model of VTEC, Compressed Sensing Tomography (CST)